Nonsteroidal Anti-Inflammatory Drugs and Opioids in Postsurgical Dental Pain. (July 2020) - Hersh, E.V.; Moore, P.A.; Grosser, T.; Polomano, R.C.; Farrar, J.T.; Saraghi, M.; Juska, S.A.; Mitchell, C.H.; Theken, K.N.
Postsurgical dental pain is mainly driven by inflammation, particularly through the generation of prostaglandins via the cyclooxygenase system. Thus, it is no surprise that numerous randomized placebo-controlled trials studying acute pain following the surgical extraction of impacted third molars have demonstrated the remarkable efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen, naproxen sodium, etodolac, diclofenac, and ketorolac in this prototypic condition of acute inflammatory pain. Combining an optimal dose of an NSAID with an appropriate dose of acetaminophen appears to further enhance analgesic efficacy and potentially reduce the need for opioids. In addition to being on average inferior to NSAIDs as analgesics in postsurgical dental pain, opioids produce a higher incidence of side effects in dental outpatients, including dizziness, drowsiness, psychomotor impairment, nausea/vomiting, and constipation. Unused opioids are also subject to misuse and diversion, and they may cause addiction. Despite these risks, some dental surgical outpatients may benefit from a 1- or 2-d course of opioids added to their NSAID regimen. NSAID use may carry significant risks in certain patient populations, in which a short course of an acetaminophen/opioid combination may provide a more favorable benefit versus risk ratio than an NSAID regimen.